2014
DOI: 10.9790/2402-08248994
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Activities of Few Lysosomal Enzymes in the Kidney and Intestine of Mice Exposed to Low Concentrations of a PCB, Aroclor 1254 under in vitro condition

Abstract: Polychlorinated biphenyls (PCBs) are industrial POPs which have been released into the environment resulting in widespread and persistent contamination. The aim of the present investigation was to determine the alterations in the activities of few lysosomal enzymes (acid phosphatase, α-galactosidase, βgalactosidase and β-glucuronidase) in lysosomal cellular sub-fractions of kidney and intestine of mice after the exposure to different concentrations of Aroclor 1254 (25 µg/ml, 50 µg/ml and 100 µg/ml) for two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In in vitro conditions, Aroclor 1254 comes in direct contact with the lysosomal enzymes and inhibit the activities while under in vivo condition, the toxicant is possibly comes into contact with the lysosomal enzymes via indirect ways. It is possible that the PCB passes through the cellular metabolic pathways and produces the hazardous metabolites which come into contact with these enzymes and induce the observed effects in the enzyme activity [7,25]. The overall results of the present study revealed that these alterations in the activities of lysosomal enzymes of mice liver and brain may create the cellular disturbances that affect the normal functional activities of lysosomes such as intracellular digestion and recycling of macromolecules [2].…”
Section: Resultsmentioning
confidence: 91%
“…In in vitro conditions, Aroclor 1254 comes in direct contact with the lysosomal enzymes and inhibit the activities while under in vivo condition, the toxicant is possibly comes into contact with the lysosomal enzymes via indirect ways. It is possible that the PCB passes through the cellular metabolic pathways and produces the hazardous metabolites which come into contact with these enzymes and induce the observed effects in the enzyme activity [7,25]. The overall results of the present study revealed that these alterations in the activities of lysosomal enzymes of mice liver and brain may create the cellular disturbances that affect the normal functional activities of lysosomes such as intracellular digestion and recycling of macromolecules [2].…”
Section: Resultsmentioning
confidence: 91%